Analysis the Implementation of Indonesian Supertax Deduction Incentive for Apprenticeship and Training Programs - Nugraeni, Usti; Saptono, Prianto Budi (International Journal Labs, 2023)
Background: In Indonesian National Medium Term Development Plan (Rencana Pembangunan Jangka Menengah/RPJMN IV) from 2020-2024, one of the Indonesian Government's agenda is increasing the quality and competitiveness of the Indonesian human resources. The available labour force is considered adequate. Based on BPS data, Indonesian labour force numbers have kept growing and reached more than 144 million in 2022, with a participation rate of around 69,06%. Aim: The research would like to analyze the implementation of Indonesian supertax deduction incentive for apprenticeship and training programs. Method: This study uses a post-positivism paradigm. This study is descriptive. This study is based on the policy performance evaluation criteria by William Dunn using Nugroho's dimensions and indicators of policy effectiveness. Both theories can explain the evaluation of policies and provide comprehensive information. Findings: The STD incentive policy for apprenticeship and training programs has been implemented in Indonesia since 2019 through the issuance of GR 45/2019 and PMK 128/2019. As of September 2022, only 65 taxpayers have received approval for the application for this tax facility. Among the 65 taxpayers, only 14 taxpayers have received tax benefits from using the STD incentive facility. Of the five criteria for public policy effectiveness, namely the right policy, the right implementation, the right on target, the right environment, and the right on process have been fulfilled.